Implementasi Kebijakan Pendidikan Inklusif di Kecamatan Koto Tangah Kota Padang - Indah Afrelia Edison; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
Inclusive education is an effort to provide equal opportunities for all students, including students with special needs, to obtain fair and non-discriminatory educational services. This study aimed to analyze the implementation of inclusive education policies and identify the factors influencing their implementation in Koto Tangah Subdistrict, Padang City. This study used a qualitative approach with a descriptive research design. Data were collected through interviews, observation, and documentation with informants consisting of representatives from UPTD LDPI, school principals, teachers, and parents of students. The results showed that, in the curriculum aspect, schools used the Kurikulum Merdeka without written modifications; however, in practice, teachers adjusted learning and assessment according to the abilities of students with special needs. In the aspect of teaching staff, there were still limitations in teachers’ understanding and skills in inclusive education, and the availability of Special Guidance Teachers (GPK) was not yet evenly distributed across all schools. In the aspect of facilities and infrastructure, the available facilities were still general in nature and did not fully support the needs of students with special needs, particularly in terms of accessibility for persons with disabilities. The factors influencing the implementation of inclusive education included communication, resources, implementers’ attitudes, and bureaucratic structure. These findings confirm that the implementation of inclusive education in Koto Tangah Subdistrict has been supported by several policy-related factors but still requires strengthening in the equitable distribution of information, improvement of teacher competence, availability of human resources, and provision of more inclusive facilities and infrastructure. The implications of this study indicate the importance of coordination among stakeholders in strengthening the implementation of inclusive education policies so that educational services for students with special needs can operate more optimally.